The development of educational system of Afganistan - M. Y. Zaki; N. U. Shedenova (Хабаршы. Психология және социология сериясы, 2013)
Afghanistan education history began with Islamic background and Islamic education system started from Maktab Khana (Mosque school) and High level were in Madrasa. Modern education was developed in the 1950s and continued in the 1960s and 1970s. Until the 60s and 70s decade of 20th century the number of madrasa’s were limited but by 80s decade with the follow up of Russian Invasion in Afghanistan the number of madrasas increased. Many of the modern governmental schools were destroyed and kid were banned form going to governmental school in order not to be influ- enced by communist ideology. During Taliban regime especially between 1994 to 2001 traditional education was the only educational structure which was supported by government; but after the fall of Taliban the number decreased and the modern education got priority for the government and shut down many schools, especially for girls in the South and East, and some science subject replaced to religious subject. Unfortunately, Afghanistan experienced periods of con- flict, especially during the last two decades of the twentieth century, which had a devastating effect on Afghan society, and its social and economic infrastructure, including education.